1997
DOI: 10.1093/emboj/16.17.5455
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+-mediated GTP-dependent dynamic assembly of bacterial cell division protein FtsZ into asters and polymer networks invitro

Abstract: FtsZ, a tubulin‐like GTPase that forms a dynamic ring marking the division plane of prokaryotic cells, is essential for cytokinesis. It is not known what triggers FtsZ ring assembly. In this work, we use a FtsZ–green fluorescent protein (Gfp) chimera to assay FtsZ assembly over time by using fluorescence microscopy. We show that FtsZ polymers can assemble dynamically in solution in a GTP‐dependent manner. Initially, FtsZ nucleation centers grow into aster‐like structures that dramatically resemble microtubule … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

25
239
2

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(266 citation statements)
references
References 43 publications
25
239
2
Order By: Relevance
“…Secondly, we examined the well-characterized effects of calcium on FtsZ polymerization. Addition of calcium at 10 mM to FtsZ polymerization assays inhibits the GTPase activity and causes bundling of polymers, resulting in hugely increased light-scattering (Mukherjee & Lutkenhaus, 1999;Scheffers et al, 2000;Yu & Margolin, 1997). We demonstrate that calcium has the same effect on FtsZ polymers in the presence of the GTP-regeneration system (Fig.…”
mentioning
confidence: 52%
See 1 more Smart Citation
“…Secondly, we examined the well-characterized effects of calcium on FtsZ polymerization. Addition of calcium at 10 mM to FtsZ polymerization assays inhibits the GTPase activity and causes bundling of polymers, resulting in hugely increased light-scattering (Mukherjee & Lutkenhaus, 1999;Scheffers et al, 2000;Yu & Margolin, 1997). We demonstrate that calcium has the same effect on FtsZ polymers in the presence of the GTP-regeneration system (Fig.…”
mentioning
confidence: 52%
“…FtsZ is strongly related to a/b-tubulin in terms of threedimensional structure (Lowe & Amos, 1998), the possession of GTPase activity (de Boer et al, 1992;Mukherjee et al, 1993;RayChaudhuri & Park, 1992) and the ability to polymerize in a nucleotide-dependent manner in vitro (Erickson et al, 1996;. Indeed, FtsZ forms a variety of polymeric structures in vitro depending on experimental conditions (Erickson et al, 1996;Lowe & Amos, 1999, 2000Yu & Margolin, 1997); however, all of these represent different arrangements of linear protofilaments.There have been multiple studies of the dynamics of FtsZ polymerization in vitro. In the presence of GDP (Rivas et al, 2000(Rivas et al, , 2001 Sossong et al, 1999) or in the presence of GTP under particular conditions where only single protofilaments are formed (Romberg et al, 2001), polymerization is proposed to be isodesmic.…”
mentioning
confidence: 99%
“…This bundling can be induced by several factors, such as Ca 2+ (REF. 21), macromolecular crowding 22 and the binding of partner proteins such as ZipA 23 (see FIG. 3).…”
Section: Structure and Assembly Of Ftszmentioning
confidence: 99%
“…This is due to the small size of the septum and the high protein density near the septum. In the meantime, in vitro experiments have found a number of FtsZ polymers (Bramhill and Thompson, 1994;Mukherjee and Lutkenhaus, 1994;Erickson, 1995;Yu and Margolin, 1997;Lu et al, 1998;Mukherjee and Lutkenhaus, 1998;Trusca et al, 1998;Löwe and Amos, 1999) that may be related to the in vivo polymer, although it should be kept in mind that in vivo FtsZ polymerisation may be guided by additional factors. Single, curved filaments have been obtained by polymerising FtsZ in solution in the presence of GTP (Lu et al, 1998(Lu et al, , 2000Mukherjee and Lutkenhaus, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…When performed on a lipid monolayer, FtsZ polymerisation yielded minirings . Sheets of laterally aligned filaments have been obtained under many conditions: in the presence of Ca ++ (Yu and Margolin, 1997;Löwe and Amos, 1999), DEAE dextran , and GTP alone. A low resolution three-dimensional reconstruction of Ca ++ -induced M. jannaschii FtsZ sheets revealed that they are composed of antiparallel double protofilaments (Löwe and Amos, 1999).…”
Section: Introductionmentioning
confidence: 99%